1992
DOI: 10.1139/x92-123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of verbenone enantiomers and racemic endo-brevicomin on response of Dendroctonusfrontalis (Coleoptera: Scolytidae) to attractant-baited traps

Abstract: Different enantiomeric ratios and elution rates of the inhibitor pheromones verbenone and racemic endo-brevicomin were evaluated for their effects on the numerical response of the southern pine beetle, Dendroctonusfrontalis Zimm., to attractant-baited traps. Enantiomeric ratios and elution rates of verbenone were important factors in inhibiting response of male D. frontalis. Deterrence was most effective for enantiomeric ratios of verbenone containing 34 and 50% of the (+) enantiomer. Using a 34% (+): 66% (−) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
2

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 0 publications
1
28
2
Order By: Relevance
“…Intertrap spacing of less than 30 m is typical for studies evaluating bark beetle semiochemicals (Payne et al 1978b;Bedard et al 1980;Bakke 1981;Borden et al 1987;Miller and Borden 1992;Sullivan 2005) and was 25 and 15-20 m in the only two trapping studies that both observed endo-brevicomin inhibition for D. frontalis and reported these experimental parameters (Payne et al 1978a;Salom et al 1992). Catch in the control traps of these tests was possibly enhanced by the nearby endo-brevicomin baits (i.e., attached to experimental traps) leading to the conclusion that the endo-brevicomin was reducing catch in the experimental trap to which it was attached.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Intertrap spacing of less than 30 m is typical for studies evaluating bark beetle semiochemicals (Payne et al 1978b;Bedard et al 1980;Bakke 1981;Borden et al 1987;Miller and Borden 1992;Sullivan 2005) and was 25 and 15-20 m in the only two trapping studies that both observed endo-brevicomin inhibition for D. frontalis and reported these experimental parameters (Payne et al 1978a;Salom et al 1992). Catch in the control traps of these tests was possibly enhanced by the nearby endo-brevicomin baits (i.e., attached to experimental traps) leading to the conclusion that the endo-brevicomin was reducing catch in the experimental trap to which it was attached.…”
Section: Discussionmentioning
confidence: 98%
“…Studies performed with racemic endo-brevicomin indicated that this compound acts as an attractant antagonist (Vité and Renwick 1971;Payne et al 1978a;Salom et al 1992). In contrast, baits composed of pure (+)-endo-brevicomin (only enantiomer produced by the species) strongly enhanced attraction to combinations of frontalin and host odors (Vité et al 1985;Sullivan et al 2007), and led these authors to conclude that this compound was a component of the D. frontalis aggregation pheromone.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier behavioural studies with racemic endo-brevicomin (often released in combination with its exo-isomer) deployed in traps generally indicated that it was a potent attraction or landing inhibitor for both sexes of D. frontalis (Payne et al, , 1978aRicherson and Payne, 1979;Salom et al, 1992b;Vit e and Renwick, 1971). Furthermore, across a wide range of concentrations it prevented arrestment by walking males over artificial gallery entrances releasing female-associated attractant .…”
Section: Endo-brevicominmentioning
confidence: 99%
“…It is possible that early trapping studies did not detect the synergistic properties of endo-brevicomin for D. frontalis because of insufficient distance among traps and the practice by researchers of performing lure comparison trials inside or near active infestations because these locations could more readily provide statistically meaningful numbers of beetle trap catches (Payne et al, 1978a,b;Salom et al, 1992b). One implication of these findings more generally for bark beetle semiochemical research is that field experiments with unrecognized multifunctional semiochemicals could be interpreted as indicating either inhibitory/repellent or synergistic/attractive properties for the test compound depending on trap spacing (Sullivan and Mori, 2009).…”
Section: Endo-brevicominmentioning
confidence: 99%
“…Evidence that male-produced endo-brevicomin and verbenone function as antiaggregation pheromones includes: (1) production solely or predominantly by the second-arriving sex Hughes 1973), (2) the ability to inhibit attraction of D. fiontalis to traps baited with frontalin plus trans-verbenol and/or host-compounds (Renwick and VitC 1970;VitC and Renwick 1971 ;Payne et al 1978;Salom et al 1992), and (3) the ability of devices releasing these compounds to reduce the numbers of beetles landing on hosts Payne and Richerson 1979) or stop the expansion of individual D. frontalis infestations . However, Billings (1985) reported that low release rates of endo-brevicomin and verbenone enhanced attraction of flying D. frontalis.…”
Section: Introductionmentioning
confidence: 99%